Problems of Law Enforcement Against Drug Users (Decision Study Number: 214/Pid.Sus/2024/PN.Mdn) - Tiur Melia, Roslina; Azhali Siregar, Mhd. (PT. Multidisciplinary Press Indonesia, 2025)
The distribution and abuse of narcotics are serious national issues that the government considers a threat to the nation’s moral integrity. Perpetrators of narcotics crimes often receive sentences from the courts that do not align with justice or legal certainty. In narcotics cases, key articles such as Articles 114, 112, and 127 of Law Number 35 of 2009 on Narcotics are commonly used. However, Articles 112 and 127 are often criticized for their vague formulations, leading to multiple interpretations. These ambiguities allow drug dealers to disguise themselves as victims, which may result in lighter sentences and contribute to legal injustice. This research adopts a normative legal approach, systematically analyzing court decisions and applicable laws to understand the criminal sanctions imposed on narcotics offenders. The study found that law enforcement in narcotics cases faces significant challenges, with a strong reliance on criminal penalties. The study further highlights the need for enhanced efforts at local, national, and international levels to combat narcotics-related crimes. In the specific case studied, the Medan District Court sentenced the defendant, Veri Suriana, to six years in prison and a fine of one billion rupiah. Failure to pay the fine would result in an additional six-month prison sentence.